Polyoxometalates (POMs): from electroactive clusters to energy materials - Horn, Michael R; Singh, Amandeep; Alomari, Suaad; Goberna-Ferrón, Sara; Benages-Vilau, Raúl; Chodankar, Nilesh; Motta, Nunzio; Ostrikov, Kostya (Ken); MacLeod, Jennifer; Sonar, Prashant; Gomez-Romero, Pedro; Dubal, Deepak (Energy & environmental science, 2021)
Polyoxometalates (POMs) represent a class of nanomaterials, which hold enormous promise for a range of energy-related applications. Their promise is owing to their "special" structure that gives POMs a truly unique ability to control redox reactions in energy conversion and storage. One such amazing capability is their large number of redox active sites that arises from the complex three-dimensional cluster of metal-oxide ions linked together by oxygen atoms. Here, a critical review on how POMs emerged from being molecular clusters for fundamental studies, to next-generation materials for energy applications is provided. We highlight how exploiting the versatility and activity of these molecules can lead to improved performance in energy devices such as supercapacitors and batteries, and in energy catalyst applications. The potential of POMs across numerous fields is systematically outlined by investigating structure-property-performance relationships and the determinant factors for energy systems. Finally, the challenges and opportunities for this class of materials with respect to addressing our pressing energy-related concerns are identified. Polyoxometalates as anionic molecular metal oxides clusters with open frameworks and rich redox chemistry have outstanding versatility in energy conversion and storage research.